Evaluation of the Hospital Wastewater Activated Sludge Extended Aeration System in the Removal of Estrogenic Compounds (Case Study: Khuzestan Hospitals) - A. Takdastan; N. Orooji; M. Noori Sepehr (Bihdād, 2016)
Background and Objective: Estrogen is a steroid hormone that is in the water and cause risks for aquatic organisms, especially fish is. Estrogenic hormones naturally (caused by endocrine) or artificial (due to hormonal contraceptives such as birth control pills) to sewage and hospital to find. This study aimed to determine the amount of estrogen in the sewage and Golestan and Abuzar hospital in Ahvaz were studied.